Parameter Sensitivity of Shallow-Bias Tunnel with a Clear Distance Located in Rock - Xueliang Jiang; Feifei Wang; Hui Yang; Jiayong Niu (Advances in Civil Engineering)
In order to obtain the seismic internal force response laws of a shallow-bias tunnel with a small clear distance, the reliability of the numerical simulation is verified by the shaking table model test. The parameter sensitivity of the tunnel is studied by using MIDAS-NX finite element software. The effects of seismic wave peak (0.1 g, 0.2 g, 0.3 g, 0.4 g, 0.5 g, and 0.6 g), existing slope angle (30°, 45°, 60°, and 90°), clear distance (1.0 D, 1.5 D, 2.0 D, and 3.0 D), and excitation mode (X direction, Z direction, XY direction, and XYZ direction) on the internal force response law of the tunnel are studied, respectively. The results show that (1) the shear force gradually increases with the increasing of seismic peak. The amplification is different with different measuring points. (2) Under different existing slope-angle conditions, the variation trend of shear force of the tunnel is similar, but the shear force is different. The existing slope has significant effect on the shear force response of the tunnel, and the degree is different with different slope angles. (3) Under the conditions of 1.5 D and 2.0 D, the shear force response of the tunnel is stronger, but the response of other conditions is relatively weak. The tunnel with 1.5 D to 2.0 D clear distance should be avoided. Different excitation modes have a significant effect on the shear force response of the tunnel. (4) Under the same excitation mode, the different excitation directions also have a significant effect on the shear force response. (5) The shear force response of the tunnel crosssection shows nonlinear variation trend. The shear force response is strongest at the arch shoulder and arch foot of the tunnel. The research results provide a useful reference for the design of antishock and vibration resistance of the tunnel.